Psikologi dalam Perilaku-perilaku Manusia Menurut Pandangan Al-Qur’an - Ahmad Farid; Ajeng Aladini Qolby; Sarmunah (JURNAL ILMIAH RESEARCH STUDENT, 2023)
In the Qur’an, human personality is seen as something unique and complex, including physical, psychological and spiritual aspects. This journal uses a psychological approach in analyzing Al-Quran verses related to personality, and shows how the Al-Quran emphasizes the importance of balance between these aspects in forming a healthy and positive personality. In this case, the Koran provides moral and ethical guidance that can help individuals develop a good and moral personality.